The Impact of Covid-19 Pandemic on Regional Economy: Supply-Driven Interregional Input-Output (IRIO) Approach for East Java Province - Defy Oktaviani; Sugeng Triwibowo; Susiyanti (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The COVID-19 pandemic mitigation measures have led to supply and demand-side labor market shock. By employing the Supply-Driven Interregional Input-Output (IRIO) approach, we estimate the impact of that labor shock on the regional economy. The model is based on the 2020 Indonesian IRIO Table, the updated version of the 2016 IRIO Table with RAS procedures. The IRIO table consists of 34 provinces and 17 sectors. Referring to our estimation, the labor shock in East Java Province has reduced the output, value-added, and employment in East Java Province by 97 trillion rupiahs, 49.41 trillion rupiahs, and 532,066 labor, respectively. Manufacturing, Wholesale and Retail Trade, as well as Accommodation and Food Service Activities, are the most adversely impacted sectors. Due to sectoral and regional interrelationships, the shock in East Java has influenced the other provinces, ultimately provinces on Java Island and in aggregate, it has reduced national output by 130.02 trillion rupiahs, shrunk the national value-added by 66.37 trillion rupiahs, and forced the 646,999 workers out of jobs with the sectoral impact has a similar pattern to the impact of East Java.